Solidifikasi/Stabilisasi (S/S) Fly Ash yang Terkontaminasi Fenol sebagai Bahan Subtitusi dan Pengisi pada Pembuatan Beton - Fatimah; Muhammad Zikir (Jurnal Teknik Kimia USU, 2023)
This study aims to assess the potential use of fly ash burning coal as a substitution and materials to making concrete filler. Material used in this study were fly ash waste product from PT. SOCI MAS, phenol, Portland cement type I, sand, gravel, and water.The use of fly ash as a substitution done with the variation in the percentage of 0%, 5 %, 10 %, 20 %, and 30 % of the weight of a cement used, and the use of fly ash as a filler material was carried out adding percentage variation of, 0%, 20 %, 40 %, 60 and 65 % of the weight of a cement used.The parameters for concrete are maximum load, compressive strength, water absorption, phenol analysis test amd loose weight metal after solidification/stabilization. The best result of using fly ash as a substitution acquired at 10 % substitution that produces a maximum load of 680 kN, strong press of 32840 MPa, and the water adsorption of 1.275 %, and as a filler best results obtained on the use of the 65 filler % that produces a maximum of 825 kN and strong press of 39.494, and the water adsorption of 0,123 % MPa. The results of the analysis free phenol and metal such as Zn, Cu, Ba are 0.003 ppm, 0.010 ppm, 0.022 ppm, 0.170 ppm.